Asian countries go for green economy - Carteciano, Joselito A.; Science Council of Asia (SCA) Conference 2012 Bogor, Indonesia).
The article is a summary of the 12th Science Council of Asia (SCA) Conference held on July 12, 2012 at Bogor, Indonesia with the theme "Mobilizing Science Towards Green Economy" and participated by 16 Asia Pacific countries including the Philippines. One of the most significant event of the conference is the establishment of the Coalition for Green Economy.
Keywords: Green technology -- Asia; Green technology -- Cost effectiveness; Green technology -- Developing countries -- International cooperation; Green technology -- Economic aspects -- Developed countries; Economic development -- Environmental aspects -- International cooperation; Environmental protection -- Economic aspects -- Asia; Conservation of natural resources -- Economic aspects -- Developing countries; Environmental protection -- Economic aspects -- Developing countries; Coalition for Green Economy